Rapid high-resolution three-dimensional mapping of T1 and age-dependent variations in the non-human primate brain using magnetization-prepared rapid gradient-echo (MPRAGE) sequence - Liu, Junjie V.; Bock, Nicholas A.; Silva, Afonso C. (NeuroImage (Orlando, Fla.), 2011)
The use of quantitative T1 mapping in neuroscience and neurology has raised strong interest in the development of T1-mapping techniques that can measure T1 in the whole brain, with high accuracy and precision and within short imaging and computation times. Here, we present a new inversion-recovery (IR) based T1-mapping method using a standard 3D magnetization-prepared rapid gradient-echo (MPRAGE) sequence. By varying only the inversion time (TI), but keeping other parameters constant, MPRAGE image signals become linear to exp(−TI/T1), allowing for accurate T1 estimation without flip angle correction. We also show that acquiring data at just 3 TIs, with the three different TI values optimized, gives maximum T1 precision per unit time, allowing for new efficient approaches to measure and compute T1. We demonstrate the use of our method at 7 T to obtain 3D T1 maps of the whole brain in common marmosets at 0.60mm resolution and within 11min. T1 maps from the same individuals were highly reproducible across different days. Across subjects, the peak of cerebral gray matter T1 distribution was 1735±52ms, and the lower edge of cerebral white matter T1 distribution was 1270±43ms. We found a significant decrease of T1 in both gray and white matter of the marmoset brain with age over a span of 14years, in agreement with previous human studies. This application illustrates that MPRAGE-based 3D T1 mapping is rapid, accurate and precise, and can facilitate high-resolution anatomical studies in neuroscience and neurological diseases. ► Using the standard MPRAGE sequence without modification for rapid 3D T1 mapping. ► Acquiring data at just 3 inversion times optimizes T1 SNR per unit imaging time. ► Accurate marmoset whole-brain T1 maps obtained at 0.6mm within 11min at 7T. ► T1 decreases with age in both gray and white matter of the non-human primate.